Penaid Nonproliferation Hindering the Spread of Countermeasures Against Ballistic Missile Defenses - Speier, Richard H. (RAND Corporation, 2014)
An attacker's missile-borne countermeasures to ballistic missile defenses are known as penetration aids, or penaids. To support efforts to prevent the proliferation of penaid-related items, this research recommends controls on potential exports according to the structure of the international Missile Technology Control Regime.